Comparison Of The Effectiveness Of Akidah Akhlak Learning With The Geschool Platform And Google Classroom - Sutipyo Ru’iya; Yusron Masduki (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study intends to describe the online learning process during the Covid-19 period at Madrasan Aliyah Negeri (MAN)